Alfabetização científica nos anos iniciais do ensino fundamental: um estudo à luz da aprendizagem dialógica e da matriz freiriana sobre percepções descritas por docentes - Crnkovic, Paula Cristina Garcia Manoel (2024)
This study presents an analysis of three publications in which the authors are teacher-researchers who developed, applied and evaluated pedagogical practices in Science Teaching through investigation aiming at scientific literacy in the early years of Elementary School. We seek to identify in the reports present in these publications the teaching-learning process within a perspective that has dialogical learning and the freirian matrix as its theoretical foundations. The question that guided the study: "How do Science teachers in the Initial Years of Elementary School understand the acquisition of scientific literacy both from their pedagogical practices based on teaching through inquiry and from the transformations they observed in their students?" also outlined its objectives, the literature review to theoretically support the field of Science Education and the methodological procedure. Due to the characteristics of qualitative research, Bardin's content analysis technique was adopted to collect and analyze the data. To identify patterns in these contents, nine codes were assigned and subsequently distributed into two categories: 1. transformations that teachers observe in children and 2. Transformative pedagogical practices. Within the first category, dialogicity emerged as fundamental followed by argumentative skills; the acquisition of these capabilities was analyzed as part of the transformations observed in students that not only allow them to express and articulate their ideas, but also make them more active. As for the second category, the contextualization of scientific concepts was the one that stood out most among the reports, as teacher-researchers understand that it is a way of articulating students' knowledge in promoting scientific literacy. Problematizing pedagogical practices were also seen as transformative because they are operationalized through dialogue and encouragement of curiosity. Teachers understand that research-based teaching integrating interdisciplinarity and the STS/STSE approach are promoters of scientific literacy and, as they include issues such as dialogicity, contextualization, problematization, collectivity, we infer that they bring similarities with the theories of dialogical learning and the freirean matrix. The study reinforces the importance of practices based on intentions structured in pedagogical knowledge with a view to a liberating, critical, reflective education aiming to promote more effective and meaningful scientific literacy from the first school years.